The role of emotional regulation ability, personality, and burnout among Spanish teachers - Castillo-Gualda, Ruth; Herrero, Marta; Rodríguez-Carvajal, Raquel; Brackett, Marc; Fernández-Berrocal, Pablo (American Psychological Association, 2019)
We aimed to gain a better understanding of the personality-burnout process by examining the effects of emotional regulation ability through both cross-sectional and a pre-post social and emotional learning intervention studies. The sample was composed of 243 Spanish public school teachers. Data were collected using the Maslach Burnout Inventory–Educators Survey, the Big Five Inventory, and the Mayer–Salovey–Caruso Emotional Intelligence Test. Our results indicated that emotional regulation ability significantly influences the effect of personality on Personal Accomplishment, a positive dimension of the Maslach Burnout Inventory. Although copious amounts of research have linked Big Five personality traits and burnout, to our knowledge this is the first study that has studied associations between personality and burnout, including a social and emotional learning intervention program aimed at reducing burnout. Considering that intra- and interpersonal emotional management are core demands on teachers, our results show the relevance of developing intervention programs focused on social and emotional abilities.
Keywords: Profesores - Aspectos psicológicos - España; emotional regulation; burnout; teachers; personality